Pemanfaatan Digital Marketing Terhadap Pengembangan Bisnis Kue Khas Padang Kresh Cookies - Heru Saputra; Ilfa Stephane; Monanda Rio Meta; M. Dahniel (Indonesia Bergerak : Jurnal Hasil Kegiatan Pengabdian Masyarakat, 2024)
This research aims to address the challenges faced by SMEs in adapting to the changing business environment, particularly with the influence of digital technology on consumer behavior. Through the utilization of product photography in visual marketing, the Padang traditional cake business, Kresh Cookies, successfully creates high product appeal and reaches a wider market. The research methodology includes market analysis, target audience identification, photography training and editing, social media management, and market research. The findings reveal an increase in brand awareness, consumer interest, and engagement on social media. This research provides guidance for other SMEs in developing their businesses through the utilization of product photography in visual marketing.